Effect of plantation depth and density on the growth and yield in sweet corn (Zea mays saccharata Strut) - Ghadeer Rashid Mohammad; Sami Mohammed Amin (Zanco Journal of Pure and Applied Sciences, 2022)
The study was carried out to determine the differences in vegetative and yield characteristics of sweet corn (Zea mays L.). at different plant density and planting depths using Nelder wheel design, this design is used to create a continuous pattern of plant densities through sowing seeds on the circumference of concentric circles of varying radians, whereas five plant densities in addition to two buffer circles were sown at different depths., conducted according to a RCBD with Nelder wheel design in four replications for the both location Grda-Rasha and Hamza-kor regain in Kurdistan- Iraq. The result of the research shows that Hamza kor location was dominant in most studied traits over Grdarasha location. While different depths had no significant effect on the studied traits. It was determined that plant density positively affected each of node pedicel-1 and internode pedicel-1 of sweet corn. Nelder design is often applied to minimize the necessity of areas required area for the experiments, due to their simplicity and wider range of scale; Nelder circles are excellent for basic spacing for operational plantations. References: Abd, M.S., Hamed, Z.A. and Ghadir, M.A., 2021, November. Response of Maize Hybrids and Inbred to Yield and its Components Under Irrigation Interval. In IOP Conference Series: Earth and Environmental Science (Vol. 904, No. 1, p. 012003). IOP Publishing. Aziz, E.K. and Al-Bawee, A.S.H., 2019. Effect of space between plants and planting depths on growth and yield of maize (Zea mays L.). Plant Archives, 19(2), pp.4434-4440. Dhangada, J.B., Tumbare, A.D. and Surve, U.S., 2021. Effect of fertigation levels and schedules on productivity and economics of maize (Zea mays)-chickpea (Cicer arietinum) cropping sequence Donald, C.M. and Hamblin, J., 1976. The biological yield and harvest index of cereals as agronomic and plant breeding criteria. In Advances in agronomy (Vol. 28, pp. 361-405). Academic Press. Duncan, D.B., 1955. Multiple range and multiple F tests. Biometrics, 11(1), pp.1-42. Hameed, S.M.A.M.P. and Ismaiel, M.N.B., 2010 Comparison among Some Italian Breeder Durum Wheat Varieties and the Locally Adapted Acsad 65 Durum Wheat. Hamid, E.A. and Adra, L. 2011. Effect of plant density and nitrogen fertilization on some yellow maize growth indicators (Basel II hybrid) and its productivity. Journal of Damascus University for Agricultural Sciences., 27 (1): 65 -81. (in Arabic) .(c.f Aziz and Al-Bawee, 2019) Imholte, A.A. and Carter, P.R., 1987. Planting Date and Tillage Effects on Corn Following Corn 1. Agronomy Journal, 79(4), pp.746-751. Kleinhenz, M.D., 2003. Sweet corn variety trials in Ohio: recent top performers and suggestions for future evaluations. HortTechnology, 13(4), pp.711-718. Kumar, B., Karjagi, C.G., Jat, S.L., Parihar, C.M., KR, Y., Singh, V., Hooda, K.S., Dass, A.K., Mukri, G., Sekhar, J.C. and Kumar, R., 2011. Maize biology: An Introduction. Mead, R., 1979. Competition experiments. Biometrics, pp.41-54. Mohammed, A.A., Majid, Z.M., Kasnazany, S.A.S., Salih, S.J., Mustafa, S.B. and Salih, O.A., 2017. Growth and yield quality of sweet corn, as influenced by nitrogen fertilization levels in Sulaimani region. The Iraqi Journal of Agricultural Science, 48(6), pp.1582-1589. Mohammed, A.A.K. and Al-Rayes , A. 1982. Plant Physiology, Part II, France (in Arabic). (c.f Aziz and Al-Bawee, 2019) Nelder, J.A., 1962. New kinds of systematic designs for spacing experiments. Biometrics, pp.283-307. Parrott, D.L., Brinks, J.S. and Lhotka, J.M., 2012. Designing Nelder wheel plots for tree density experiments. New forests, 43(2), pp.245-254. Radosevich, S.R., 1987. Methods to study interactions among crops and weeds. Weed Technology, 1(3), pp.190-198. Randle, W.M., Davis, D.W. and Groth, J.V., 1984. The effects of corn leaf rust on maturity and quality of fresh market ears of sweet corn [Puccinia sorghi, Minnesota]. Journal American Society for Horticultural Science. Scott, C.E. and Eldridge, A.L., 2005. Comparison of carotenoid content in fresh, frozen and canned corn. Journal of food Composition and Analysis, 18(6), pp.551-559. Shaheenuzzamn, M., Saha, R.R., Ahmed, B., Rahman, J. and Salim, M., 2015. Green cob and fodder yield of sweet corn as influenced by sowing time in the hilly region. Bangladesh Journal of Agricultural Research, 40(1), pp.61-69. Sharifi, R.S., Sedghi, M. and Gholipouri, A., 2009. Effect of population density on yield and yield attributes of maize hybrids. Res. J. Biol. Sci, 4(4), pp.375-379. Szymanek, M., Dobrzański jr, B., Niedziółka, I. and Rybczyński, R., 2005. Sweet corn: harvest and technology physical properties and quality. B. Dobrzański Institute of Agrophysics Polish Academy of Aciences. Ugur, A. and Maden, H.A., 2015. Sowing and planting period on yield and ear quality of sweet corn (Zea mays L. var. saccharata). Ciência e Agrotecnologia, 39, pp.48-57. Zhu, S., Mount, J.R. and Collins, J.L., 1992. Sugar and soluble solids changes in refrigerated sweet corn (Zea mays L). Journal of food science, 57(2), pp.454- 457.